Combined spinal-epidural and general anesthesia for cesarean section in pregnant with placenta percreta - Moreira, Adriano; Sampaio, Catarina; Faria, Aida (Journal of the Portuguese Society of Anesthesiology, 2014)
We describe a case of a pregnant woman with a previous diagnosis of placenta percreta, submitted to a combined spinal-epidural and general anesthesia for cesarean section with hysterectomy. The procedure was performed using the placement of balloon catheters in the common iliac arteries in order to minimize uterine perfusion during the hysterectomy and thus prevent major blood loss.